1996
DOI: 10.1577/1548-8659(1996)125<0760:rbbsaa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Size and Anaerobic Metabolism in Brook Trout and Largemouth Bass

Abstract: The relationship between body size, anaerobic capacity, and white muscle acid‐base and metabolite status was examined for two sizes of brook trout Salvelinus fontinalis and largemouth bass Micropterus salmoides. Resting muscle lactate, pH, HCO3−, and partial pressure of carbon dioxide (Pco2) were size‐independent in brook trout. After exercise, however, there was a significant positive relationship between the accumulation of both lactate and metabolic protons and body size in brook trout. In addition, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
4
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 25 publications
3
26
4
1
Order By: Relevance
“…Fish appear to have greater long-term survival following tournaments that were conducted when ambient water temperatures were cooler. Further, smaller sized fish appear to be more resilient to tournament-related stressors that result in mortality as compared to larger fishes, regardless of ambient water temperature or livewell additive; they experience less physiological disturbance because they are often played for shorter periods of time and endure shorter periods of air exposure during weigh-in procedures (Kieffer et al 1996;Ostrand et al 1999;Cooke et al 2002). Collectively, these results suggest that the addition of livewell additives does not enhance fish survival following competitive angling events.…”
Section: Discussionmentioning
confidence: 99%
“…Fish appear to have greater long-term survival following tournaments that were conducted when ambient water temperatures were cooler. Further, smaller sized fish appear to be more resilient to tournament-related stressors that result in mortality as compared to larger fishes, regardless of ambient water temperature or livewell additive; they experience less physiological disturbance because they are often played for shorter periods of time and endure shorter periods of air exposure during weigh-in procedures (Kieffer et al 1996;Ostrand et al 1999;Cooke et al 2002). Collectively, these results suggest that the addition of livewell additives does not enhance fish survival following competitive angling events.…”
Section: Discussionmentioning
confidence: 99%
“…In general, metabolic acid production during anaerobic exercise positively scales with body size in active fish such as the rainbow trout (Goolish 1991;Ferguson et al 1993) and brook Kieffer et al 1996). This relationship is probably due to the greater anaerobic energy demands that larger fish are forced to contend with during burst swimming (Goolish 1991).…”
Section: Acid-base and Ionoregulationmentioning
confidence: 99%
“…Houlihan et al (1984) reported similar effects of hypoxia on the walking performance of Carcinus maenas, and an increased anaerobic scope with increasing body size is also known, for example, in brown trout Salvelinus fontinalis (Kieffer et al 1996) and rainbow trout Oncorhynchus mykiss (Ferguson et al 1993 Table 7. Carcinus maenas, Mytilus edulis.…”
Section: Smaller Crabsmentioning
confidence: 84%